Wide crosses of Vigna food legumes - Ng, N.Q. (1992)
Many successful wide crosses among Asiatic cultivated Vigna species and between them and a wild species, V. trilobata, have been reported However, despite many attempts to cross the African cultivated Vigna species with wild Vigna species and the Asiatic cultivated Vigna species, there has been no success as yet. Nevertheless, crosses between cultivated and wild subspecies of V. unguiculata were fairly easy and their hybrids are fertile. Studies conducted at the International Institute of Tropical Agriculture (IITA) have shown that crossing barriers between V. unguiculata and several African wild Vigna species were due to abortion ofyoung embryos and pollen-pistil incompatibility. With more basic research on reproductive biology and tissue culture, and a larger number of crosses among species and genotypes, there will be a greater chance of success for wide crosses between V. unguiculata and wild Vigna species which possess some very desirable traits for the improvement of this cultivated species